(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
ABSTRACT: The impact of artificial intelligence systems has renewed reflection on civil liability, prompting jurists to identify approaches capable of securing fair and effective remedies. The paper reconstructs possible criteria for attributing harm, ranging from product liability to the rules laid down by Art. 2050 of the Italian Civil Code, and foregrounds risk as a parameter for calibrating remedial responses. The general clause in Art. 2043 of the Civil Code remains the minimum framework of protection. Alongside this, the paper considers whether no-fault compensation schemes might be introduced to manage the cost of AI-related harm.